Core Competencies of School Administrators in Mueang Sa Kaeo District under the Sa Kaeo Primary Educational Service Area Office 1 - อยู่แท้กูล, สุรวุฒิ; รูปสุวรรณกุล, ปัทมา; กลิ่นเกษร, อุษาพร; บุญนาค, ลลิต (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were to: 1) study the core competencies of school administrators in Mueang Sa Kaeo District under the Sa Kaeo Primary Educational Service Area Office 1  2) compare the core competencies of school administrators as perceived by teachers, classified by educational level, work experience, and school size; and  3) explore guidelines for developing the core competencies of school administrators in Mueang Sa Kaeo District under the Sa Kaeo Primary Educational Service Area Office 1. The sample consisted of 237 teachers in the academic year 2025 (B.E. 2568). The research instrument was a five-point rating scale questionnaire with a reliability coefficient of 0.98. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, and F-test.           The research findings revealed that: 1. The core competencies of school administrators in Mueang Sa Kaeo District under the Sa Kaeo Primary Educational Service Area Office 1 were at a high level, both overall and in each aspect.  2. Teachers with different educational levels and work experience did not significantly differ in their overall perceptions of the core competencies of school administrators. However, teachers working in schools of different sizes showed statistically significant differences in their overall perceptions at the .05 level. 3. Guidelines for developing the core competencies of school administrators should emphasize analytical and synthetic skills to enhance effective performance with optimal use of resources. Data-based decision-making, participatory management, and maximizing the use of available resources are key factors contributing to successful school administration.